THE MODERN CONDITION OF PROBLEM OF EMOTIONAL BURNOUT IN THE PSYCHOLOGICAL SCIENCE - V. Knyazev; K. Remizova (Вестник университета)
The article describes the emotional burnout. The author’s analyzes various theories and come to the conclusion that various factors at work can lead this syndrome. In addition, the article reveals the ways how to fight this syndrome - the different kinds of training exercises, seminars and lectures will help here.